Advantages of Whole Genome Sequencing in Mitigating the Helicobacter pylori Antimicrobial Resistance Problem - Kartika Afrida Fauzia; Ricky Indra Alfaray; Yoshio Yamaoka (Microorganisms, 2023)
Helicobacter pylori antimicrobial resistance is a critical public health issue. Typically, antimicrobial resistance epidemiology reports include only the antimicrobial susceptibility test results for H. pylori. However, this phenotypic approach is less capable of answering queries related to resistance mechanisms and specific mutations found in particular global regions. Whole genome sequencing can help address these two questions while still offering quality control and is routinely validated against AST standards. A comprehensive understanding of the mechanisms of resistance should improve H. pylori eradication efforts and prevent gastric cancer.